Konsep dan Teori-Teori Kepemimpinan Islam - Hidayah, Nurul; Harahap, Agneis Novirieka; Ibnopita, Ibnopita; Muhtarom, Ubed; Tobroni, Tobroni (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
Abstract: In this life, you need a leader to lead, guide and manage life because a leader is considered someone who can do these things. Leadership is a classic topic of discussion, but it is still very interesting to study because it determines the continuity of an organization. Leadership is essentially accountability, so a leader must understand the concepts and theories of leadership itself. From this, the purpose of this article research is to understand the concepts and theories of leadership. The type of research used is library research. The data collection technique uses documentation, which is a way to obtain data and information in the form of books and journal documents that can support research. The results of this research study show that the concept of leadership in Islam is identical to the term khalifa which means representative. Besides the caliph is also called Ulil Amri, which means the highest leader in Islamic society. In Islam, a person who becomes a leader must meet six requirements, namely: having strength, trustworthiness, the conscientiousness of conscience, being professional, not taking opportunities, and placing the most suitable and appropriate person. Thus, according to Islam, the ideal leader is fair, trustworthy, fathonah, shiddiq, qona'ah, siyasah, and patient. To be a leader, of course, it is not easy; there must be concepts and theories of leadership that are understood to be able to carry out their duties and have an impact on the surrounding environment. Therefore, it is important to understand the concepts and theories of leadership in life to be able to become a responsible leader and protect its members.